Establishment and Characterization of a Human Small Cell Osteosarcoma Cancer Stem Cell Line: A New Possible In Vitro Model for Discovering Small Cell Osteosarcoma Biology - Gaia Palmini; Roberto Zonefrati; Cecilia Romagnoli; Alessandra Aldinucci; Carmelo Mavilia; Gigliola Leoncini; Alessandro Franchi; Rodolfo Capanna; Maria Luisa Brandi (Stem Cells International)
Osteosarcoma (OSA) is the most common primary malignant bone tumor, usually arising in the long bones of children and young adults. There are different subtypes of OSA, among which we find the conventional OS (also called medullary or central osteosarcoma) which has a high grade of malignancy and an incidence of 80%. There are different subtypes of high grade OS like chondroblastic, fibroblastic, osteoblastic, telangiectatic, and the small cell osteosarcoma (SCO). In this study, for the first time, we have isolated, established, and characterized a cell line of cancer stem cells (CSCs) from a human SCO. First of all, we have established a primary finite cell line of SCO, from which we have isolated the CSCs by the sphere formation assay. We have proved their in vitro mesenchymal and embryonic stem phenotype. Additionally, we have showed their neoplastic phenotype, since the original tumor bulk is a high grade osteosarcoma. This research demonstrates the existence of CSCs also in human primary SCO and highlights the establishment of this particular stabilized cancer stem cell line. This will represent a first step into the study of the biology of these cells to discover new molecular targets molecules for new incisive therapeutic strategies against this highly aggressive OSA.